Antibacterial Activity of Gaharu (Aquilaria malaccensis Lamk) Against the Bacteria Streptococcus pyogenes - Elianto, Nopriani; Sianturi, Sister; Saharuddin, Tria Saputra (Faculty of Agriculture, Tompotika Luwuk University, 2025)
Streptococcus pyogenes is a bacterium that causes throat and skin infections. Diseases caused by Streptococcus pyogenes bacteria can typically be treated with antibiotics. This study aims to determine the antibacterial activity of the ethanol extract of gaharu leaves (Aquilaria malaccensis Lamk) against the development of Streptococcus pyogenes bacteria using the disc diffusion method. The positive control used the antibiotic clindamycin, and the negative control used 1% DMSO. Observations were made by measuring the inhibition zone formed around the paper disc. The average diameter of the inhibition zone formed included a 10% concentration of 9.8 mm, a 15% concentration of 10.08 mm, a 20% concentration of 11.54 mm, and for the positive control, antibiotic clindamycin, it was 29.92 mm in the very strong category. In contrast, the negative control, 1% DMSO, did not form an inhibition zone. The One Way Anova data analysis test using the SPSS IBM version 26 program obtained results (p>0.05), meaning that there were significant antibacterial and differences in the diameter of the inhibition zone of the ethanol extract of gaharu leaves in each treatment.